Unmanned Rotorcraft Systems - Cai, Guowei. (Advances in Industrial Control, 2011)
Unmanned Rotorcraft Systems explores the research and development of fully-functional miniature rotorcraft unmanned aerial vehicles (UAV), and provides a complete treatment of their design. The unmanned system is an integration of advanced technologies developed in communications, computing, and control areas. It is a useful testing ground for trialing and implementing modern control techniques despite the challenges introduced by the limitations on direct scalability between the systems of a small-scale rotorcraft and those of its full-scale counterpart. Included are detailed expositions of: systematic hardware construction; software systems integration; aerodynamic modeling; and automatic flight control system design. Emphasis is placed on the cooperative control and flight formation of multiple UAVs, vision-based ground-target tracking, and landing on moving platforms. Other issues such as the development of indoor micro aerial vehicles (that have to operate without access to a global positioning system) and vision-based navigation are also discussed in depth. The text is rounded out with a presentation of possible future research directions for relevant fields of study. Unmanned Rotorcraft Systems will be of great value to practicing engineers in aerospace-related industries and to academic researchers from aerospace, electrical or mechanical engineering backgrounds working on the development of unmanned systems.